Condition Index, Reproduction and Feeding of Three Non-Obligatory Riverine Mekong Cyprinids in Different Environments - Natkritta Wongyai; Achara Jutagate; Tuantong Jutagate; Chaiwut Grudpan (Tropical Life Sciences Research, 2020)
Condition index, reproduction and feeding of three non-obligatory riverine Mekong cyprinids namely Hampala dispar, Hampala macrolepidota and Osteochilus vittatus were examined. The samples were from the Nam Ngiep (NN) River and Bueng Khong Long (BKL) Swamp, which are the representative of the lotic- and lentic-environments, respectively. These two habitats lay in the same geographical area but on the opposite banks of the Mekong mainstream. The samplings were conducted between May 2017 and April 2018. There were 365 H. dispar, 259 H. macrolepidota and 298 O. vittatus samples in this study. The condition index of all three species were beyond 90% implying they can live well in both lotic and lentic environments. Reproductions of all three species were taken place in both environments with two peaks at the onset and end of rainy season. The samples from BKL showed early maturation than NN samples in all three (3) species. Feeding plasticity, though dominant by insects, was observed in Hampala spp., while O. vittatus can utilise any available detritus in both environments. Results clearly show that all the three selected non-obligatory riverine fish species can live very well in either lotic or lentic environments and imply that they can adjust themselves to reservoir environment.